Fiscal stability of the local government units in the Republic of Srpska - Biljana Gojković; Sanja Popović; Marijana ukić (Economic Themes, 2021)
Fiscal stability of the local self-government units is the condition for stable public finances of the Republic of Srpska (hereinafter: RS) as a whole. Stable public finances of local self-government units have a positive impact on the economic growth of the RS. Therefore, it is necessary to pay a significant attention to the fiscal problems of local self-government units (hereinafter: LGUs). Although the public finances of the LGUs make up 15% of the total public finances of the Republic of Srpska, it is important to emphasize that the life of the RS citizens takes place in the local self-government. In this regard, LGUs have the important role in providing public goods and services, as well as creating the environment for the life of citizens on the basis of legally defined competencies. Having in mind the importance and role of local self-government units in the RS, it is necessary to ensure the efficient management and stability of their public finances. One of the preconditions for the successful exercise of the competencies of LGUs is the rational and efficient use of available resources. The aim of this paper is to examine the impact of the key fiscal factors of local self-government units on their fiscal stability. The results of this analysis will provide answers to the question of how rational and efficient local self-government units are in the execution of their competencies and how it is reflected on their revenues and expenditures, i.e. in total public finances of RS.
Keywords: H70; H72; H74; 330; Republic of Srpska; local self-government units; fiscal stability